Pelakasanaan Ganti Rugi Pengadaan Tanah Menurut Undang-Undang Nomor 2 Tahun 2012 - Prasdhana, Aga; Huda, Miftakhul (UNES Law Review, 2024)
This article aims to analyze the implementation of compensation in land acquisition for public development in accordance with Law Number 2 of 2012 and to examine the legal resolution mechanisms when there is a refusal of the type or amount of compensation offered. The issue centers on how compensation is implemented for land ownership for development purposes as stipulated by Law Number 2 of 2012, and the legal mechanisms for resolution when landowners reject the form and/or amount of the established compensation. To approach this issue, the theoretical framework used is derived from Law Number 2 of 2012 on Land Procurement for Public Interest and Article 18 of the Basic Agrarian Law. Data was collected through normative research methods (literature studies) by reviewing legal materials through a legislative approach. Thus, in this study, secondary data is prioritized, while primary data (field observation results) are used only as supplementary information. The data are analyzed qualitatively. This study concludes that compensation for land acquisition must be fair and given to the rightful parties. If there is a rejection of the type or amount of compensation offered, the landowner can file an objection to the local district court within 14 working days after the signing of the meeting report.